Expression dynamics of the tomato rbcS gene family during development. - Wanner, L A (1991)
The tomato rbcS gene family is composed of five genes (rbcS1, 2, 3A, 3B, and 3C) that are differentially expressed during tomato development. Nuclear run-on transcription assays and RNA analysis were used to determine the contribution of transcriptional and post-transcriptional regulation to the accumulation of mRNA from the five rbcS genes in tomato seedlings, leaves, and fruit. We found that the qualitative pattern of mRNA accumulation is regulated at the transcriptional level and that, in general, there is a correlation of rates of rbcS transcription with overall rbcS mRNA abundance in fruit and leaves. Although transcriptional control is a primary determinant for rbcS gene expression in tomato, examination of relative transcription rates and mRNA accumulation of each rbcS gene demonstrated that there is also significant post-transcriptional control of rbcS gene expression during organ development. Individual rbcS mRNAs, which have highly conserved coding sequences and differ only in their 5' and 3' untranslated sequences, have different stabilities. We showed that both transcription and stability of individual rbcS mRNAs are altered in different organs and by the developmental program within these organs as well as by exposure to light. Together, the results provide a comprehensive analysis of the extent of transcriptional and post-transcriptional control that operates within the rbcS gene family during plant development.